1998
DOI: 10.1023/a:1009243917844
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This work was undertaken to analyse the effects of acute cadmium administration on the pulsatile pattern of prolactin release, in adult male rats. For this purpose, animals were cannulated 40 h before the experiment to allow a continuous blood withdrawal. Two hours after the administration of one dose of cadmium chloride (4.5 mg kg1), the pulsatile pattern of prolactin, during three hours, was studied. The effects of two pulses of thyrotropin-releasing hormone (TRH) (1 microgram per rat), given 60 and 120 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Cadmium effectively depressed prolactin in both in vivo and in vitro studies (14,15,22). Such inhibitory effect could be explained by the decreased amplitude of prolactin peaks reported elsewhere (13). Cadmium may act directly on the lactotrophs, through an interaction with the prolactin molecule, that is sensitive to divalent metals, as was shown in vitro (22).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Cadmium effectively depressed prolactin in both in vivo and in vitro studies (14,15,22). Such inhibitory effect could be explained by the decreased amplitude of prolactin peaks reported elsewhere (13). Cadmium may act directly on the lactotrophs, through an interaction with the prolactin molecule, that is sensitive to divalent metals, as was shown in vitro (22).…”
Section: Discussionmentioning
confidence: 70%
“…Cadmium may act directly on the lactotrophs, through an interaction with the prolactin molecule, that is sensitive to divalent metals, as was shown in vitro (22). However, previous studies in vivo indicated a normal response of prolactin to the thyrotropin releasing hormone (TRH) in cadmium-treated rats (13), thus indicating a differential intracellular kinetics of cadmium in vivo as compared to the in vitro studies using cultures of pituitary cells (22). The effects of the metal on D A at the median eminence would be suggestive of increased rather than decreased plasma prolactin levels, considering the well known inhbitory role of DA on prolactin (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations